‘Butta Kodi, Biné Kodi’: Stigma dan Dampaknya Terhadap Tu Tamanang di Kabupaten Gowa - Mirawati - Syam; Nurul Ilmi Idrus (ETNOSIA : Jurnal Etnografi Indonesia, 2017)
Tu tamanang is a Makassar term for bad soil (butta kodi) for women and bad seed (biné kodi) for men, as sexual intercourse is analogised with planting (lamung-lamung). Whether or not one is considered as tu tamanang is not based on biomedical check-up, but simply on the basis ofmarital duration (5 years and more) and the attributes attached to tu tamanang which may be different by gender. The importance of the existence of children in the family has caused social stigma among tu tamanang. Such stigma is based on the  attributes that can be observed, the gendered parable, the reproductive health-related perception towards the couple, and the label that tu tamanang are infortune persons. In dealing with such social stigma, tamanang women tend to be passive, while men are more aggressive, by showing their refusal to stigma through polygyny or divorce to get married. However, women also become agents in regard to divorce and polygyny. But, refusal towards social stigma is also the case for couple who does not problematised lack of children in the family, and tamanang is not simply a source of conflict. Stigma towards tu tamanang significantly affects the social life of tu tamanang, which is classified into 3 categories: self-isolation, demanding divorce and polygyny. There is a need to educate the society regarding the cause of infertility and how to deal with it, since existing various stigma against tu tamanang are based on social perception, which are non-medical and presumption. In addition, since biomedical service is not the main priority for tu tamanang, they need relevant information regarding existing service and service procedures because even though they access medical service, it has never been continued. This is because accessing medical service is identical with handling of various documents which they consider rather complicated.